Epistemological Disjunctivism and the Random Demon Hypothesis - Lockhart, Thomas (International journal for the study of skepticism, 2018)
According to epistemological disjunctivism I can claim to know facts about the world around me on the basis of my perceptual experience. My possession of such knowledge is incompatible with a number of familiar skeptical scenarios (for example, that I am currently being deceived by an evil demon). So a paradigmatic epistemological disjunctivist perceptual experience should allow me to rule out such incompatible skeptical scenarios. In this paper, I consider skeptical scenarios which both cast doubt on my conviction that I can trust my purported perceptual experiences and appear to be compatible with my enjoying a veridical perceptual experience of my environment. Such skeptical scenarios draw attention to a significant difference between McDowell’s epistemological disjunctivism and Pritchard’s. McDowellian epistemological disjunctivism has the resources to rule out such skeptical scenarios but Pritchard’s does not. This is because the Pritchardian epistemological disjunctivist does not, unlike McDowell, insist on the idea that perception is a fallible capacity, self-consciously exercised and possessed, for knowledge.